Changing theories of change: strategic shifting in implicit theory endorsement - Leith, Scott A.; Ward, Cindy L. P.; Giacomin, Miranda; Landau, Enoch S.; Ehrlinger, Joyce; Wilson, Anne E. (My University, 2014)
People differ in their implicit theories about the malleability of characteristics such as intelligence and personality. These relatively chronic theories can be experimentally altered, and can be affected by parent or teacher feedback. Little is known about whether people might selectively shift their implicit beliefs in response to salient situational goals. We predicted that, when motivated to reach a desired conclusion, people might subtly shift their implicit theories of change and stability to garner supporting evidence for their desired position. Any motivated context in which a particular lay theory would help people to reach a preferred directional conclusion could elicit shifts in theory endorsement. We examine a variety of motivated situational contexts across 7 studies, finding that people’s theories of change shifted in line with goals to protect self and liked others and to cast aspersions on disliked others. Studies 1–3 demonstrate how people regulate their implicit theories to manage self-view by more strongly endorsing an incremental theory after threatening performance feedback or memories of failure. Studies 4 – 6 revealed that people regulate the implicit theories they hold about favored and reviled political candidates, endorsing an incremental theory to forgive preferred candidates for past gaffes but leaning toward an entity theory to ensure past failings “stick” to opponents. Finally, in Study 7, people who were most threatened by a previously convicted child sex offender (i.e., parents reading about the offender moving to their neighborhood) gravitated most to the entity view that others do not change. Although chronic implicit theories are undoubtedly meaningful, this research reveals a previously unexplored source of fluidity by highlighting the active role people play in managing their implicit theories in response to goals.
Keywords: implicit theories; incremental; entity; motivated reasoning